2021
DOI: 10.3390/cryst11091014
|View full text |Cite
|
Sign up to set email alerts
|

Diagonalization Method to Hyperbolic Two-Temperature Generalized Thermoelastic Solid Sphere under Mechanical Damage Effect

Abstract: This study is the first to use the diagonalization method for the new modelling of a homogeneous, thermoelastic, and isotropic solid sphere that has been subjected to mechanical damage. The fundamental equations were derived using the hyperbolic two-temperature generalized thermoelasticity theory with mechanical damage taken into account. The outer surface of the sphere has been assumed to have been shocked thermally without cubical dilatation. The numerical results for the dynamical and conductive temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…As a result, they modified the two-temperature model to the hyperbolic twotemperature model, in which the difference between the second derivative concerning the time of the dynamical and conductive temperature is proportional to the heat supply, and found that this model introduces a thermal wave that propagates with a limited speed. Recently, [22][23][24] discussed different types of problems in the context of the HTT theory of thermoelasticity.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they modified the two-temperature model to the hyperbolic twotemperature model, in which the difference between the second derivative concerning the time of the dynamical and conductive temperature is proportional to the heat supply, and found that this model introduces a thermal wave that propagates with a limited speed. Recently, [22][23][24] discussed different types of problems in the context of the HTT theory of thermoelasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Saeed and Abbas [10] studied the hyperbolic two-temperature photothermal interaction in semiconducting mediums. Al-Lehaibi [11] studied the diagonalizations approach to hyperbolic two-temperature thermoelastic solid spheres under mechanical damage effects. Abbas et al [12] discussed the hyperbolic two-temperature photothermal interactions in semiconducting materials with cylindrical holes.…”
Section: Introductionmentioning
confidence: 99%